Statistical Convergence in Ordered Bicomplex-Valued Metric Spaces - Jaiswal, Molhu Prasad; Pahari, Narayan Prasad; Bhatta, Chet Raj; Parajuli, Purusottam (Journal of Nepal Mathematical Society, 2025)
This article presents the fundamental properties of bicomplex numbers and explores the partial order relations defined on them. It further develops bicomplex valued metric spaces based on these partial orderings and introduces a few theorems related to statistical convergence within the framework of bicomplex numbers.